Effects of Boophilus Microplus Larval Infestation on Kedah - Kelantan Cattle and Their Bos Taurus Crosses - Abdulla, Mahmood Ameen (1997)

(untitled)
Tick resistance and the effects of dexamethasone and anti-histamine were investigated in four Kedah-Kelantan (KKKK), four FI Kedah-Kelantan X Friesian (KKFF), and four 25% Kedah-Kelantan X 75% Frieisian (KFFF) using experimental tick infestations. Experimental animals were infested (20,000 larvae) on four occasions with an interval of two months between infestations to determine tick responses and haematological and cellular responses of the host. Subsequently, the effects of dexamethasone and anti-histamine were investigated. Number of ticks, their weight, weight of egg masses and number of hatched larvae were significantly (P<0.05) lower in KKKK than in their crosses. At tick attachment sites, infiltration and degranulation of eosinophils and basophils were the striking changes. KKKK expressed intense eosinophil and basophil response than their crosses. Mast cells were completely ablated at 24 h post infestation indicative of their degranulation. Animals treated with dexamethasone were susceptible to B. microplus larvae as shown by the production of a high number of engorged female ticks, high mean weight of replete ticks, mean weight of egg masses and number of larvae. There was a reduction or complete ablation of cellular infiltration particularly of eosinophils at tick feeding sites in all genotypes. There was little or no effect of anti-histamine treatment on the acquisition of resistance. On the contrary, animals treated with anti-histamine and dexamethasone became more susceptible to B. micro plus larvae. Eosinophil number was higher in anti-histamine treated than those receiving both anti-histamine and dexamethasone in all genotypes. The high tick resistance of Kedah-Kelantan (KKKK) may be attributed to reduction of ticks numbers, presence of degranulated eosinophils and basophils, the absence of immunosuppression, and release of histamine at tick attachment sites from degranulated eosinophils and basophils. Histamine initiates an immediate hypersensitivity reaction leading to self-grooming. As a result, the number of engorged ticks were reduced or absent in Kedah-Kelantan than in their crosses.